The impact of environmental, social and governance on firm performance: The mediating role of green innovation - Guo, Fei; Kadir, Hazlina Abd.; Talib, Zunirah Binti Mohd (Edelweiss Applied Science and Technology, 2025)
This study aims to investigate the impact of corporate environmental, social and governance (ESG) performance on financial performance (measured by ROA of return on total assets) and to examine the mediating role of green innovation (measured by the number of green patent applications). This paper constructs a research framework based on stakeholder theory and sustainable development theory, selects Chinese A-share listed companies as samples, and constructs a panel regression model for empirical analysis. The results of hypothesis testing show that: good ESG performance significantly enhances corporate ROA; corporate ESG performance positively promotes green innovation; green innovation positively affects ROA; and green innovation plays a partial mediating effect between ESG and ROA. The findings suggest that corporate fulfilment of ESG responsibilities can enhance economic efficiency by promoting green innovation, confirming the expectations of sustainable development and stakeholder theory, and providing empirical evidence for corporate sustainability strategies and government green policies.